2016
DOI: 10.1097/wno.0000000000000332
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery and the Neuro-Ophthalmologist

Abstract: Background As the prevalence of obesity increases, so are the prevalences of weight related diseases and the incidence of surgical procedures to promote weight loss. It is important for neuro-ophthalmologists to be familiar with these procedures and possible downstream effects on afferent and efferent visual function. Evidence acquisition Review of ophthalmology, neurology, general surgery, obesity, endocrinology, nutrition, psychiatry and neurosurgery literature. Results Bariatric surgery is a safe and ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Weight‐reduction surgery is considered for patients unable to achieve sufficient loss via diet and lifestyle changes alone . The type of procedure performed does not appear to significantly affect outcomes as long as losses are durable.…”
Section: Conservative Treatment Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Weight‐reduction surgery is considered for patients unable to achieve sufficient loss via diet and lifestyle changes alone . The type of procedure performed does not appear to significantly affect outcomes as long as losses are durable.…”
Section: Conservative Treatment Measuresmentioning
confidence: 99%
“…6 Weight-reduction surgery is considered for patients unable to achieve sufficient loss via diet and lifestyle changes alone. 11,19,20,40,60 The type of procedure performed does not appear to significantly affect outcomes as long as losses are durable. One systematic review demonstrated that up to 92% of patients undergoing bariatric surgery resolved their visual field deficits.…”
Section: Lifestyle Changes and Weight Lossmentioning
confidence: 99%
“…8 In adults with obesity-related IIH, weight reduction -either by diet or bariatric surgery -improved vision, with papilledema and IIH resolution. 9,10 Surgical interventions were associated with 100% of postoperative IIH resolution against 66.7% in the non-surgical group (95%CI 45.6-87.8; p<0.005). 11 Some authors even consider bariatric surgery as the procedure of choice for severely obese patients with IIH.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years this option has begun to gain interest because of its multiple health benefits to morbidly obese patients. 3 However, the current literature consists only of case reports or small retrospective studies that suggest that bariatric surgery is an effective treatment for pseudotumor cerebri. 1 , 4 , 5 The reports in the literature lack substantial data supporting the benefit from weight loss surgery.…”
Section: Discussionmentioning
confidence: 99%